Teachers' Perceptions Of The Implementation Of Accreditation And Its Relationship With The Quality Of Madrasah Education - Johan Andriesgo; Indra Indra; Manisha Anggela (At-Tarbiyat, 2024)
This study aims to analyze teacher perceptions of the implementation of accreditation and pit it against the quality of madrasah education. The quality of madrasah education is inseparable from the participation of teachers, who are the prominent individuals to guarantee the quality of a school/madrasah. This study uses a quantitative approach to the type of field research. The data collection technique was carried out by distributing questionnaires to State Madrasah teachers in Bengkalis. Data analysis in this study used simple linear regression analysis with Statistical Package for the Social Sciences (SPSS) 25.0 For Windows. The analysis and processing of research data show that: 1) When teachers' perceptions of the implementation of S/M accreditation are very good (positive), it will also have a positive effect on the quality of education of a madrasah. Because there is a significant relationship between teachers' perceptions of the implementation of S/M accreditation and the quality of madrasahs, 2) Internal education customers (especially principals/madrasahs, teachers and education personnel) should not assume that school/madrasah accreditation is only limited to five-year activities prepared by several months before the visitation. Moreover, the results of accreditation must be used as a reference and motivation to always improve the quality of education in schools / madrasah.